Preparation method and use method of waterproof coating and waterproof agent

By using a composite silane system to prepare waterproof coatings, the problem of insufficient waterproofing performance of single silane materials is solved, and the waterproofing performance and adhesion of concrete are significantly improved, which is suitable for waterproofing treatment of large volume concrete.

CN119286351APending Publication Date: 2025-01-10CHINA TIESIJU CIVIL ENGINEERING GROUP CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411606708.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Waterproof coatings prepared from existing single silane materials have limitations in improving the waterproof performance of concrete and cannot meet engineering needs.

Method used

Emulsifier and dispersant are dispersed in water and reacted with silane monomer to form a nanosilane emulsion, and added silica sol and nanosilia to form a composite silane system. Then, binder is added to prepare a waterproof coating, and the concrete is improved through the composite silane system. Waterproof performance.

Benefits of technology

Compared with a single silane monomer, the waterproofing agent prepared by composite silane significantly reduces the water absorption ratio of concrete, improves waterproof performance, and enhances the adhesion between the coating and the substrate, and is suitable for waterproofing treatment of large volume concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286351A_ABST
    Figure CN119286351A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and a use method of a waterproof coating and a waterproof agent, and relates to the technical field of building materials. The preparation method of the waterproof coating comprises the following steps: respectively dispersing an emulsifier and a dispersant in water, adding a silane monomer, and reacting at 20-40 DEG C for 1-2 hours to obtain a nano silane emulsion; adding silica sol and nano silicon dioxide into the nano silane emulsion, and uniformly stirring to obtain a waterproof agent; a binder is added into the waterproof agent, the waterproof coating is obtained after uniform mixing, and the waterproof agent has better waterproof performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a preparation method and a use method of a waterproof coating and a waterproofing agent. Background Art

[0002] Concrete is a porous material with nanometer to millimeter-scale micropores on its surface. The hydrophilicity of concrete makes harmful media (CO2, Cl - Water can penetrate into the concrete through capillaries, causing the durability of the concrete structure to decrease, resulting in serious economic losses. Therefore, waterproofing concrete is of great significance to improve durability.

[0003] At present, there are two most direct and simple methods to improve the waterproof effect of concrete. One is to add waterproof materials, that is, to add waterproofing agents when preparing concrete to improve the concrete's impermeability and prevent water intrusion. However, this method is only applicable to small areas of concrete. If a large volume of concrete is treated as a whole, the treatment cost will be greatly increased. The other is to use waterproof coatings to waterproof the surface of concrete, forming a protective coating, hydrophobic film, etc. on the surface of the concrete to prevent water intrusion.

[0004] Existing waterproof coatings often include silane materials. Silane materials can adjust the surface free energy of concrete, changing the concrete surface from hydrophilic to hydrophobic. However, the inventors found during the experiment that when the dosage of a single silane material reaches a certain amount, the waterproof performance of the concrete tends to be stable. At this time, increasing the dosage of the single silane material will no longer improve the waterproof performance of the concrete. Therefore, the waterproof performance provided by a single silane material to the concrete is limited and cannot meet the requirements of the project for the waterproof performance of the concrete. Therefore, providing a super hydrophobic waterproof coating for concrete has become a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing and using a waterproof coating, and a waterproofing agent, which solves the technical problem that the existing waterproof coating prepared from a single silane material has poor waterproof performance.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a waterproof coating, comprising the following steps:

[0010] S1. Preparation of waterproofing agent

[0011] S11, dispersing the emulsifier and the dispersant in water respectively, adding the silane monomer, and reacting at 20-40° C. for 1-2 hours to obtain a nano-silane emulsion;

[0012] S12, adding silica sol and nano silicon dioxide to the nano-silane emulsion, stirring evenly, to obtain a waterproofing agent;

[0013] S2. Preparation of waterproof coating

[0014] Add a binder to the waterproof agent and mix them evenly to obtain a waterproof coating.

[0015] Preferably, the emulsifier is a mixture of Peregal and Span, the mass ratio of Peregal to Span is 1:2-4, and the added amount of the emulsifier is 2-5% of the mass of the silane monomer.

[0016] Preferably, the dispersant is selected from any one of polyethylene glycol, polyvinyl alcohol and methyl cellulose, and the added amount of the dispersant is 10-25% of the mass of the silane monomer.

[0017] Preferably, the silane monomer is selected from one or more of propyltrimethoxysilane, butyltriethoxysilane and octyltriethoxysilane, and the mass ratio of the silane monomer to water is 1:1-4.

[0018] Preferably, the particle size of the silica sol is 20-30 nm, and the mass ratio of the added amount of the silica sol to the silane monomer is 1:1-1.2.

[0019] Preferably, the particle size of the nano-silicon dioxide is 50-100 nm, and the mass ratio of the added amount of the nano-silicon dioxide to the silane monomer is 1:10-10.5.

[0020] Preferably, the adhesive is selected from any one of epoxy resin, polyurethane and acrylic resin.

[0021] Preferably, the amount of the binder is 0.5-1% of the mass of the waterproofing agent.

[0022] In the second aspect, the present invention provides a waterproofing agent prepared by the waterproof coating preparation method described in the first aspect, wherein the waterproofing agent comprises a composite silane, wherein the composite silane comprises propyltrimethoxysilane, silica sol, and nano-silica, wherein the particle size of the silica sol is 20-30nm, the particle size of the nano-silica is 50-100nm, and the dosage of the composite silane is 34%-40%.

[0023] In a third aspect, the present invention provides a method for using the waterproof coating as described in the first aspect, wherein the total coating amount of the waterproof coating is 250-400 g / m 2, the total coating amount is sprayed in 2-3 times.

[0024] (III) Beneficial effects

[0025] The present invention provides a preparation method and use method of a waterproof coating and a waterproof agent. Compared with the prior art, the present invention has the following beneficial effects:

[0026] The method for preparing a waterproof coating of the present invention comprises dispersing an emulsifier and a dispersant in water respectively, adding a silane monomer, reacting at 20-40° C. for 1-2 hours, and obtaining a nano-silane emulsion; adding silica sol and nano-silicon dioxide to the nano-silane emulsion, and stirring evenly to obtain a waterproofing agent; the waterproofing agent uses a composite silane system composed of silane monomer, silica sol, and nano-silicon dioxide, and as the amount of the composite silane increases, the water absorption ratio of the prepared concrete test block gradually decreases. Under the same dosage conditions, compared with a single silane monomer, the waterproofing agent prepared using the composite silane has a lower water absorption ratio of the concrete test block, and after the dosage reaches 37.4%, the amount of the composite silane is increased, and the water absorption ratio of the concrete test block continues to decrease. Therefore, the waterproofing agent prepared using the composite silane in the present application has better waterproof performance. A binder is added to the waterproofing agent, and the mixture is evenly mixed to obtain a waterproof coating, thereby improving the bonding force between the waterproof coating and the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 is a particle size distribution diagram of the silane emulsion prepared in Example 1;

[0029] Figure 2 is a contact angle diagram of the test block after the waterproof material is applied in Example 1;

[0030] Figure 3 This is a diagram showing the waterproofing effect of the concrete test block after the waterproof material is applied in Example 1. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0033] Example 1

[0034] This embodiment provides a method for preparing a super hydrophobic protective coating for concrete, comprising the following steps:

[0035] S1. Preparation of waterproofing agent

[0036] S11. Weigh 440g of deionized water and place it in a four-necked flask. Add 1.4g of Peregal, 2.8g of Span 80 and 30g of polyethylene glycol, and stir for 10-15min to dissolve and disperse it evenly. Then weigh 120g of octyltriethoxysilane monomer and add it dropwise into the four-necked flask using a peristaltic pump set for 15min. Set the temperature to 30°C and stir at 650rpm for 1.5h to obtain a uniform nano-scale silane emulsion. Its particle size distribution is shown in the figure below. Figure 1 ;

[0037] S12, after the reaction is completed, weigh 120g of silica sol with a particle size of 30nm (SiO2 solid content of 30%) and 12g of nano-silicon dioxide with a particle size of 50nm, add them to the prepared silane emulsion, stir evenly, and obtain a waterproofing agent, in which the total mass of octyltriethoxysilane monomer, silica sol, and nano-silicon dioxide accounts for 34.7% of the mass of the waterproofing agent, that is, the amount of composite silane is 34.7%;

[0038] S2. Preparation of super hydrophobic waterproof coating

[0039] Add 6 g of epoxy resin (type E42) to the waterproofing agent and mix well to obtain a super hydrophobic waterproof coating.

[0040] Super hydrophobic waterproof coating construction method:

[0041] Apply the waterproof coating on the C30 concrete surface of 100*100*100mm according to the following specific construction process, including the following steps:

[0042] Select the concrete surface to be constructed and inspect it. If there are obvious cracks and damages, repair them. Then clean the base surface and remove the dust on the surface to ensure that the base surface is clean.

[0043] After the concrete surface is dry and there is no visible water, the waterproof coating is evenly sprayed on the concrete surface to form a protective layer. The total coating amount is about 350g / m 2 , spray twice, and cover with plastic film after completion. The curing time is 2 days, and the painted construction surface is kept from being washed by rain. After the curing is completed, the water absorption ratio of the C30 concrete test block is tested according to the following method.

[0044] Water absorption ratio: tested in accordance with JC / T 902-2002 "Organic silicon waterproofing agent for building surfaces".

[0045] Example 2

[0046] This embodiment provides a method for preparing a super hydrophobic protective coating for concrete, comprising the following steps:

[0047] S1. Preparation of waterproofing agent

[0048] S11, weigh 440g of deionized water and put it into a four-necked flask, add 1.4g of peregrin, 2.8g of Span 80 and 30g of polyethylene glycol, stir for 10-15min to make it dissolve and disperse evenly, then weigh 120g of propyltrimethoxysilane, use a peristaltic pump to set 15min to dropwise add it into the four-necked flask, set the temperature to 30°C, stir and react at a speed of 650rpm for 1.5h to obtain a uniform nano-scale silane emulsion;

[0049] S12, after the reaction is completed, weigh 120g of silica sol with a particle size of 30nm and 12g of nano-silicon dioxide with a particle size of 50nm, add them to the prepared silane emulsion, stir evenly, and a waterproofing agent can be obtained;

[0050] S2. Preparation of super hydrophobic waterproof coating

[0051] Add 6 g of epoxy resin (type E44) to the waterproofing agent and mix well to obtain a super hydrophobic waterproof coating.

[0052] The construction method of the super hydrophobic waterproof coating is the same as that of Example 1.

[0053] Example 3

[0054] S1. Preparation of waterproofing agent

[0055] S11, weigh 440g of deionized water and put it into a four-necked flask, add 1.4g of peregrin, 2.8g of Span 80 and 30g of polyvinyl alcohol, stir for 10-15 minutes to make it dissolve and disperse evenly, then weigh 120g of butyltriethoxysilane monomer, use a peristaltic pump set for 15min to dropwise add it into the four-necked flask, set the temperature to 30°C, stir and react at a speed of 650rpm for 1h to obtain a uniform nano-scale silane emulsion;

[0056] S12, after the reaction is completed, weigh 120g of silica sol with a particle size of 20nm and 12g of nano-silicon dioxide with a particle size of 100nm, add them to the prepared silane emulsion, stir evenly, and a waterproofing agent can be obtained;

[0057] S2. Preparation of super hydrophobic waterproof coating

[0058] Add 6 g of epoxy resin to the waterproofing agent and mix evenly to obtain a waterproof coating.

[0059] The construction method of the super hydrophobic waterproof coating is the same as that of Example 1.

[0060] Example 4

[0061] The difference between this embodiment and embodiment 2 is that propyltriethoxysilane is used instead of propyltrimethoxysilane, and the rest is the same as embodiment 2.

[0062] Example 5

[0063] The difference between this embodiment and embodiment 2 is that the dosage of propyltrimethoxysilane is 125, the dosage of silica sol is 125, and the dosage of nano silicon dioxide is 12.5. The other ingredients are the same as those in embodiment 2.

[0064] Example 6

[0065] The difference between this embodiment and embodiment 2 is that the dosage of propyltrimethoxysilane is 130, the silica sol is 13 nanometers and the silicon dioxide is 13, and the rest is the same as embodiment 2.

[0066] Example 7

[0067] The difference between this embodiment and embodiment 2 is that the dosage of propyltrimethoxysilane is 135, the dosage of silica sol is 135, and the dosage of nano silicon dioxide is 13.5. The other dosages are the same as embodiment 2.

[0068] Example 8

[0069] The difference between this embodiment and embodiment 2 is that the dosage of propyltrimethoxysilane is 140, the dosage of silica sol is 140, and the dosage of nano silicon dioxide is 14. The other ingredients are the same as embodiment 2.

[0070] Example 9

[0071] The difference between this embodiment and embodiment 2 is that the dosage of propyltrimethoxysilane is 145, the dosage of silica sol is 145, and the dosage of nano silicon dioxide is 14.5. The other dosages are the same as embodiment 2.

[0072] Example 10

[0073] The difference between this embodiment and embodiment 2 is that the dosage of propyltrimethoxysilane is 150, the dosage of silica sol is 150, and the dosage of nano silicon dioxide is 15. The other ingredients are the same as embodiment 2.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 1 is that in step S11, the amount of octyltriethoxysilane monomer used is 252 g, and the mass of octyltriethoxysilane monomer accounts for 34.7% of the mass of the waterproofing agent, that is, the amount of silane used is 34.7%, excluding S12, and the rest is the same as Example 1.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 2 is that the amount of propyltrimethoxysilane used in step S11 is 252 g, S12 is not included, and the rest is the same as Example 2.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 3 is that the amount of butyltriethoxysilane monomer used in step S11 is 252 g, S12 is not included, and the rest is the same as Example 3.

[0080] Comparative Example 4

[0081] The difference between this comparative example and Example 4 is that the amount of propyltriethoxysilane monomer used in step S11 is 252 g, S12 is not included, and the rest is the same as Example 4.

[0082] Comparative Example 5

[0083] The difference between this comparative example and Example 5 is that in step S11, the amount of propyltrimethoxysilane monomer used is 262.5 g, and S12 is not included. The rest is the same as Example 5.

[0084] Comparative Example 6

[0085] The difference between this comparative example and Example 6 is that the amount of propyltrimethoxysilane monomer used in step S11 is 273 g, S12 is not included, and the rest is the same as Example 6.

[0086] Comparative Example 7

[0087] The difference between this comparative example and Example 7 is that the amount of propyltrimethoxysilane monomer used in step S11 is 283.5 g, S12 is not included, and the rest is the same as Example 7.

[0088] Comparative Example 8

[0089] The difference between this comparative example and Example 8 is that the amount of propyltrimethoxysilane monomer used in step S11 is 294 g, S12 is not included, and the rest is the same as Example 8.

[0090] Comparative Example 9

[0091] The difference between this comparative example and Example 9 is that the amount of propyltrimethoxysilane monomer used in step S11 is 304.5 g, S12 is not included, and the rest is the same as Example 9.

[0092] Comparative Example 10

[0093] The difference between this comparative example and Example 10 is that the amount of propyltrimethoxysilane monomer used in step S11 is 315 g, S12 is not included, and the rest is the same as Example 10.

[0094] The water absorption ratios of the C30 concrete test blocks prepared in Examples 1-10 and Comparative Examples 1-10 are shown in Table 1.

[0095] Table 1 Water absorption ratio of C30 concrete test blocks

[0096]

[0097]

[0098] The blank group experiment was set up as follows: the blank group only cleaned the concrete surface without spraying waterproof coating. The steps of cleaning the concrete surface and other test conditions were the same as those in Example 1. The water absorption ratio of the test block is shown in Table 1.

[0099] From Table 1, comparative examples 1-10 are analyzed, and a single silane monomer is used to prepare a waterproofing agent. As the amount of the single silane monomer increases, the water absorption ratio of the prepared C30 concrete test block basically shows a trend of gradually decreasing. However, when the amount of the single silane monomer increases to 37.4%, the water absorption ratio of the C30 concrete test block tends to be stable. At this time, the water absorption ratio of the C30 concrete test block will no longer decrease when the amount of the single silane monomer is increased. Example 1-10 is analyzed, and a composite silane is used to prepare a waterproofing agent. As the amount of the composite silane increases, the water absorption ratio of the prepared C30 concrete test block basically shows a trend of gradually decreasing. However, under the same dosage conditions, compared with a single silane monomer, the water absorption ratio of the C30 concrete test block prepared using the composite silane is lower, and after the dosage reaches 37.4%, the amount of the composite silane is increased, and the water absorption of the C30 concrete test block continues to decrease. Therefore, the waterproofing agent prepared by the composite silane has better waterproof performance.

[0100] Comparative Example 11

[0101] The difference between this comparative example and Example 10 is that the particle size of the silica sol is 15 nm, and the rest is the same as Example 10.

[0102] Comparative Example 12

[0103] The difference between this comparative example and Example 10 is that the particle size of the silica sol is 18 nm, and the rest is the same as Example 10.

[0104] Comparative Example 13

[0105] The difference between this comparative example and Example 10 is that the particle size of the silica sol is 32 nm, and the rest is the same as Example 10.

[0106] Comparative Example 14

[0107] The difference between this comparative example and Example 10 is that the particle size of the silica sol is 35 nm, and the rest is the same as Example 10.

[0108] Comparative Example 15

[0109] The difference between this comparative example and Example 10 is that the particle size of the nano-silicon dioxide is 105 nm, and the rest is the same as Example 10.

[0110] Comparative Example 16

[0111] The difference between this comparative example and Example 10 is that the particle size of the nano-silicon dioxide is 108 nm, and the rest is the same as Example 10.

[0112] Comparative Example 17

[0113] The difference between this comparative example and Example 10 is that the particle size of the nano-silicon dioxide is 45 nm, and the rest is the same as Example 10.

[0114] Comparative Example 18

[0115] The difference between this comparative example and Example 10 is that the particle size of the nano-silicon dioxide is 40 nm, and the rest is the same as Example 10.

[0116] Comparative Example 19

[0117] The difference between this comparative example and Example 10 is that octyltriethoxysilane is used instead of propyltrimethoxysilane, and the rest is the same as Example 10.

[0118] Comparative Example 20

[0119] The difference between this comparative example and Example 10 is that propyltriethoxysilane is used instead of propyltrimethoxysilane, and the rest is the same as Example 10.

[0120] Comparative Example 21

[0121] The difference between this comparative example and Example 10 is that butyltriethoxysilane is used instead of propyltrimethoxysilane, and the rest is the same as Example 10.

[0122] The water absorption ratios of the C30 concrete test blocks prepared in Comparative Examples 11-21 are shown in Table 2.

[0123] Table 2 Water absorption ratio of C30 concrete test blocks

[0124]

[0125] From Table 2, comparing Example 10 and Comparative Examples 11-21, the amount of composite silane used is the same, the type of silane monomer of the composite silane, the silica sol particle size, and the nano-silica particle size are different, and the water absorption ratio of the concrete prepared in Example 10 is smaller. Therefore, the synergistic effect of propyltrimethoxysilane, silica sol particle size, and nano-silica particle size reduces the concrete water absorption ratio and improves the waterproof effect of the waterproof coating. When the silica sol particle size is 20-30nm, the nano-silica particle size is 50-100nm, and propyltrimethoxysilane exists, the water absorption rate of the concrete is relatively low, and the waterproof performance of the waterproof coating is excellent.

[0126] In order to further verify the waterproof effect of the waterproof coating prepared by the method of the present invention, the contact angle, chloride ion diffusion coefficient, and 28d carbonization depth of the C30 concrete test blocks after curing of Examples 1-3, Comparative Examples 1-2, and the blank group were tested according to the following methods, and the results are shown in Table 3. Among them, the contact angle of the test block after the waterproof material of Example 1 is applied is shown in Table 3. Figure 2 , waterproof effect diagram as shown Figure 3 . Figure 2 and Figure 3 All of these indicate that the concrete test block of Example 1 has a good waterproof effect.

[0127] Contact angle: tested according to JC / T 2168-2013 "Self-cleaning coated glass";

[0128] Chloride ion diffusion coefficient: tested in accordance with GB / T 50082-2009 "Standard for test methods of long-term performance and durability of ordinary concrete";

[0129] 28d carbonation depth: tested in accordance with GB / T 50082-2009 "Standard for test methods for long-term performance and durability of ordinary concrete".

[0130] Table 3 Performance test of C30 concrete blocks of Examples 1-3

[0131]

[0132] It can be seen that the super hydrophobic waterproof coating of the present invention can effectively improve the ability of concrete to resist chloride ion erosion, significantly reduce the carbonization depth of concrete, improve the carbonization resistance and frost resistance of concrete, and enhance the long-term durability of concrete. After brushing, compared with the untreated concrete specimen, the chloride ion diffusion coefficient is reduced by more than 80%, the 28d carbonization depth can be reduced by more than 60%, and the contact angle between water and the concrete surface can be greater than 150°; therefore, the super hydrophobic waterproof coating of the present invention not only has excellent super hydrophobic performance, but also has better durability and a wide range of applications.

[0133] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0134] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a waterproof coating, characterized in that: The following steps are involved: S1. Preparation of waterproofing agent S11, dispersing the emulsifier and the dispersant in water respectively, adding the silane monomer, and reacting at 20-40° C. for 1-2 hours to obtain a nano-silane emulsion; S12, adding silica sol and nano silicon dioxide to the nano-silane emulsion, stirring evenly, to obtain a waterproofing agent; S2. Preparation of waterproof coating Add a binder to the waterproof agent and mix them evenly to obtain a waterproof coating.

2. The method for preparing a waterproof coating according to claim 1, characterized in that: The emulsifier is a mixture of peregal and Span, the mass ratio of peregal to Span is 1:2-4, and the added amount of the emulsifier is 2-5% of the mass of the silane monomer.

3. The method for preparing a waterproof coating according to claim 1, characterized in that: The dispersant is selected from any one of polyethylene glycol, polyvinyl alcohol and methyl cellulose, and the added amount of the dispersant is 10-25% of the mass of the silane monomer.

4. The method for preparing a waterproof coating according to claim 1, characterized in that: The silane monomer is selected from one or more of propyltrimethoxysilane, butyltriethoxysilane and octyltriethoxysilane, and the mass ratio of the silane monomer to water is 1:1-4.

5. The method for preparing a waterproof coating according to claim 1, characterized in that: The particle size of the silica sol is 20-30 nm, and the mass ratio of the added amount of the silica sol to the silane monomer is 1:1-1.

2.

6. The method for preparing a waterproof coating according to claim 1, characterized in that: The particle size of the nano-silicon dioxide is 50-100 nm, and the mass ratio of the added amount of the nano-silicon dioxide to the silane monomer is 1:10-10.

5.

7. The method for preparing a waterproof coating according to claim 1, characterized in that: The adhesive is selected from any one of epoxy resin, polyurethane and acrylic acid.

8. The method for preparing a waterproof coating according to claim 1, characterized in that: The amount of the binder is 0.5-1% of the mass of the waterproofing agent.

9. A waterproofing agent prepared by the method for preparing a waterproof coating according to any one of claims 1 to 8, characterized in that: The waterproofing agent comprises composite silane, which comprises propyltrimethoxysilane, silica sol and nano silicon dioxide. The particle size of the silica sol is 20-30nm, the particle size of the nano silicon dioxide is 50-100nm, and the dosage of the composite silane is 34%-40%.

10. A method for using the waterproof coating according to claim 1, characterized in that: The total coating amount of the waterproof coating is 250-400g / m 2 , the total coating amount is sprayed in 2-3 times.

Citation Information

Patent Citations

  • Composite high-polymer waterproof paint and preparation method thereof

    CN103436159A

  • Preparation method for composite emulsion waterproof agent used for surface water prevention of raw soil wall

    CN105153872A

  • Nano-alumina modified silane waterproofing agent as well as preparation method and application thereof

    CN109679498A

  • Super-hydrophobic coating, and preparation method and application thereof, and super-hydrophobic foam concrete and preparation method for super-hydrophobic foam concrete

    CN111040625A

  • Colloidal silica dispersion

    CN1692073A